2017
DOI: 10.5014/ajot.2017.024182
|View full text |Cite
|
Sign up to set email alerts
|

A Way of Seeing: How Occupation Is Portrayed to Students When Taught as a Concept Beyond Its Use in Therapy

Abstract: Three concepts-subject-centered learning, threshold concepts, and transformative learning-formed the theoretical foundation for teaching occupation as a way of seeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…45,47,62 As they developed more discriminating perspectives, their worldviews shifted. 47,53,58,66,[96][97][98] Accordingly, TL influenced their values, attitudes and behaviours, 30,37,57,61,72,99 and how they saw and understood themselves. 14,33,69,80 Students developed new interpretations of how things were, including conditions within the realm of health care.…”
Section: Outcomes Of Transformative Learningmentioning
confidence: 99%
“…45,47,62 As they developed more discriminating perspectives, their worldviews shifted. 47,53,58,66,[96][97][98] Accordingly, TL influenced their values, attitudes and behaviours, 30,37,57,61,72,99 and how they saw and understood themselves. 14,33,69,80 Students developed new interpretations of how things were, including conditions within the realm of health care.…”
Section: Outcomes Of Transformative Learningmentioning
confidence: 99%
“…(2016, p. 485). Price, et al, (2017) focused on the teaching of occupation within occupational therapy education advocating for subject centred curricula; use of the concept of occupation as a threshold concept and use of pedagogic methods that can support transformational learning.…”
Section: Resultsmentioning
confidence: 99%
“…This results in the notable challenge for education with the core concept of occupation remaining "… a just-out-of-sight subject" (Hooper, 2006, p. 558;Krishnagiri, et al, 2017). In an attempt to redress this problem Price, et al (2017) identified "… concepts from education literature … that could support teaching occupation as a way of seeing" (p. 6), one of which is the use of threshold concepts.…”
Section: Interchangeable Terminologymentioning
confidence: 99%
“…These data sets were collected in the United States (5), Australia (2), and the United Kingdom (1). The articles by Krishnagiri et al (2017), Hooper et al (2018), Price et al (2017) and Taff et al (2018) reported different aspects of results from the same data set. Similarly Copley et al (2010Copley et al ( , 2011 and Hooper (2006aHooper ( , 2008 each reported on two articles from the same data sets.…”
Section: Study Characteristics and Critical Appraisalmentioning
confidence: 99%
“…Occupation-centered education should ensure future graduates are prepared to use occupation as the central focus of their practice (Di Tommaso et al, 2016;Fisher, 2013;Whiteford & Wilcock, 2001). Numerous articles recognize the important role that occupation-centered education plays in the transformation of the profession and emphasize the need for students to learn about occupation from both personal and practice perspectives (Hooper, 2006a;Price et al, 2017;Whiteford & Wilcock, 2001;Yerxa, 1998). Occupation must therefore be utilized as the central idea in occupational therapy education, however it is not yet known how occupation is being incorporated into education programs.…”
mentioning
confidence: 99%